PENYELESAIAN SENGKETA PEMUTUSAN HUBUNGAN KERJA (PHK) ANTARA SUHARDI DIBYO TRISWORO DAN CV. SATRIA BUANA SAKTI: Settlement of Termination of Employment (PHK) Dispute between Suhardi Dibyo Trisworo and CV. Satria Buana Sakti - Putradianto, Mochammad Fauzan; Pamungkas, Yogo (Faculty of Law, Universitas Trisakti, 2025)
This study discusses the settlement of the Termination of Employment (PHK) dispute between Suhardi Dibyo Trisworo and CV. Satria Buana Sakti which was decided through Cassation Decision Number 615 K/Pdt.Sus-PHI/2024. The legal issues discussed include the inconsistency of the implementation of the unilateral termination of employment by the company, which is contrary to applicable laws and regulations, namely Law Number 11 of 2020 concerning Job Creation and Government Regulation Number 35 of 2021. The analysis shows that termination of employment must be carried out in accordance with legal procedures and accompanied by timely notification. In addition, the neglect of workers' rights to receive compensation, such as severance pay and length of service awards, is also the focus of the discussion. In conclusion, the actions of CV. Satria Buana Sakti do not comply with applicable legal provisions, which have the potential to harm workers' rights. The recommendation put forward is the need for stricter law enforcement against companies that carry out termination of employment without following the correct procedures and providing workers' rights in accordance with existing regulations.